Evaluation of Safety and Health Conditions in Large Scale Construction Projects - Salek Zamankhani, Jalal (European Journal of Sustainable Development, 2018)
In the past decade, a lot of studies and researches have been done on the problems concerning the management of safety and health in construction sites. But, there are very few studies discussing the issue in project environment from viewpoint of workers. Especially, safety and health management, which has been usually subject of the empiricism, is not considered deeply on the large scale construction sites in Iran. However, it is necessary to understand the quantitative mechanism of safety and health in project site to proceed the necessary management technique properly, and set up the suitable strategies by trade-off of risk and cost to reduce the safety and health risk during construction of the project. In this paper, employees of several large scale construction projects in metropolitan areas of Tabriz were randomly selected and were asked to respond the NOSACQ questionnaire. The results showed that safety and health management in large scale construction sites are relatively acceptable. Besides, the perception of safety and health was found to have no special association with age, work experience, education, but instead the creation of a safety climate depends on the approach of people higher in the organizational hierarchy of the project. Keywords: construction, health, safety, sustainability.